2021
DOI: 10.1007/s11207-021-01894-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Spectroscopy of a Non-adiabatic Solar Atmosphere

Abstract: The quantification of all possible waves and instabilities in a given system is of paramount importance, and knowledge of the full magnetohydrodynamic (MHD) spectrum allows one to predict the (in)stability of a given equilibrium state. This is highly relevant in many (astro)physical disciplines, and when applied to the solar atmosphere it may yield various new insights in processes like prominence formation and coronal loop oscillations. In this work we present a detailed, high-resolution spectroscopic study o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…• Does coronal rain exclusively correspond to unstable thermal modes? In the complex solar atmosphere, it has been shown that unstable modes can have mixed properties, and that all MHD modes may become unstable (Claes and Keppens, 2021;Zavershinskii et al, 2021). This is linked to the observed morphology of clumps, as discussed above.…”
Section: Numerical Sidementioning
confidence: 84%
See 1 more Smart Citation
“…• Does coronal rain exclusively correspond to unstable thermal modes? In the complex solar atmosphere, it has been shown that unstable modes can have mixed properties, and that all MHD modes may become unstable (Claes and Keppens, 2021;Zavershinskii et al, 2021). This is linked to the observed morphology of clumps, as discussed above.…”
Section: Numerical Sidementioning
confidence: 84%
“…Non-adiabatic MHD spectroscopy codes are now available, such as "Legolas" , that take into account thermal misbalance and allow to quantify the stability of the wave modes in onedimensional setups. Using this tool, Claes and Keppens (2021) show that thermal instabilities are unavoidable in the solar atmosphere, and that all modes (thermal, slow and fast) may exhibit unstable behaviour.…”
Section: Local Scales: Thermal Instabilitymentioning
confidence: 99%
“…those from modern plasma physics textbooks focusing on MHD spectroscopy (Goedbloed, Keppens & Poedts 2019). A typical application can be found in Claes & Keppens (2021), where it was shown that especially the effect of radiative cooling in a realistic, magnetised solar atmosphere model yields MHD eigenspectra dominated by thermal instabilities and magneto-thermal overstabilities.…”
Section: Introductionmentioning
confidence: 99%
“…During the heating, chromospheric evaporation occurs, and the loop gets dense and starts to radiate strongly. During the cooling, catastrophic cooling can occur, leading to thermal instability (TI) locally in the corona (Claes & Keppens 2021). TI is thought to generate cool and dense condensations called rain clumps, which subsequently fall as coronal rain toward the surface under the action of various forces (Oliver et al 2014;Fang et al 2015).…”
Section: Introductionmentioning
confidence: 99%